Answer:
Step-by-step explanation:
If you let b = x^2 the problem becomes a whole lot easier. Note that x = √b
x^2 + x - 12
Now factor this trinomial.
(x + 4)(x - 3)
Now put b back into the equation
(√b + 4)(√b - 3)
-x-1
all you do is subtract 9x from 8x.
Answer: 2 1/3
Explanation:
10 2/6 - 7 5/6
You can make both a fraction by multiplying the denominator by the whole number, and then adding the numerator to that number, and keeping the denominator the same. So, 10*6 = 60 and 60 + 2 = 62 and you keep the denominator as 6, which would make 62/6
7*6 = 42 and 42 + 5 = 47 so 7 5/6 becomes 47/6
10 2/6 is equivalent to 62/6
7 5/6 is equivalent to 47/6
This just makes it easier to look at.
Now you just work through the equation.
62/6 - 47/6 = 15/6
15/6 = 2 3/6 = 2 1/3
Answer:
And we can find this probability like this:
And we can replace the values and we got:
Step-by-step explanation:
For this case we define the random variable Y as: the number of slices of cheesecake left on the platter after the first serving. And we have the following distribution for Y:
Y | 0 1 2 3 4
P(Y) | 0.005 0.114 0.429 0.381 0.071
And we want to find the following probability:
And we can find this probability like this:
And we can replace the values and we got: